The Pressure‐Induced Polymorphic Transformations in Fluconazole. Issue 12 (14th September 2015) - Gorkovenko, Ekaterina A.; Kichanov, Sergey E.; Kozlenko, Denis P.; Belushkin, Alexandr V.; Wąsicki, Jan; Nawrocik, Wojciech; Mielcarek, Jadwiga; Dubrovinsky, Leonid S.; Lathe, Christian; Savenko, Boris N.
Abstract : The structural properties and Raman spectra of fluconazole have been studied by means of X‐ray diffraction and Raman spectroscopy at pressures up to 2.5 and 5.5 GPa, respectively. At a pressure of 0.8 GPa, a polymorphic phase transition from the initial form I to a new triclinic form VIII has been observed. At higher pressure of P = 3.2 GPa, possible transformation into another new polymorphic form IX has been detected. The unit cell parameters and volumes, and vibration modes as functions of pressure have been obtained for the different forms of fluconazole. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4164–4169, 2015